Reductive, Coenzyme A-Mediated Pathway for 3-Chlorobenzoate Degradation in the Phototrophic Bacterium Rhodopseudomonas palustris - Egland, Paul G. (American Society for Microbiology, 2001)
We isolated a strain of Rhodopseudomonas palustris (RCB100) by selective enrichment in light on 3-chlorobenzoate to investigate the steps that it uses to accomplish anaerobic dechlorination. Analyses of metabolite pools as well as enzyme assays suggest that R. palustris grows on 3-chlorobenzoate by (i) converting it to 3-chlorobenzoyl coenzyme A (3-chlorobenzoyl–CoA), (ii) reductively dehalogenating 3-chlorobenzoyl–CoA to benzoyl-CoA, and (iii) degrading benzoyl-CoA to acetyl-CoA and carbon dioxide. R. palustris uses 3-chlorobenzoate only as a carbon source and thus incorporates the acetyl-CoA that is produced into cell material. The reductive dechlorination route used by R. palustris for 3-chlorobenzoate degradation differs from those previously described in that a CoA thioester, rather than an unmodified aromatic acid, is the substrate for complete dehalogenation.